Comprehensive analysis of radiologic cancer-free (rCF) status through various treatment approaches in advanced-stage hepatocellular carcinoma - Keisuke Koroki; Sadahisa Ogasawara; Ryo Izai; Takuya Yonemoto; Teppei Akatsuka; Chihiro Miwa; Sae Yumita; Masanori Inoue; Kazufumi Kobayashi; Soichiro Kiyono; Masato Nakamura; Naoya Kanogawa; et al. (Liver Cancer, 2024)
Introduction In the realm of oncology, the pinnacle of therapeutic success is achieving a state where the patient is entirely free of cancer, i.e. ‘cancer-free’. This benchmark should not only apply to early-stage malignancies but should also be the standard aim for advanced-stage diseases, including hepatocellular carcinoma (HCC). However, there is a glaring gap in the research landscape concerning the understanding of what cancer-free status truly means for advanced-stage HCC. Our study sheds light on the profound implications of reaching a cancer-free by radiological assessments in patients with advanced-stage HCC. Methods We established a database tracking the full clinical course of all patients with HCC (from 2003–2022). We identified the initial instances of macrovascular invasion or extrahepatic spread. We defined radiologic cancer-free (rCF) as cases in which no recurrence was observed for at least 2 months following curative treatment or complete response to systemic therapies. The frequency of achieving rCF status was investigated, categorised by patients’ background. Results We identified 795 patients with advanced-stage HCC. The rCF rate was 8.7%. Patients who achieved rCF status had significantly better prognoses compared to those who did not (p < 0.001). In the decision tree analysis, the number of tumors ≥8 was the strongest factor making it difficult to achieve rCF status. Analysis of stage progression patterns revealed varying background characteristics at the time of advanced-stage diagnosis, with discrepancies in rCF rates. Conclusions Despite the low rate of achieving rCF status, the prognostic impact was significant. Patients with certain tumor characteristics had a higher likelihood of achieving rCF status. The distribution of tumor conditions varies based on the pattern of progression, which affects the likelihood of achieving a rCF status.